A study of the output characteristics of electric fuel pumps during artificial fault simulation - Gritsenko A. (FME Transactions, 2021)
The electric fuel pump (EFP) is one of the potential sources of fuel system failures. According to various data, the fuel system accounts for 25...50% of all failures. The most common reason for the impairment of the fuel system performance and, in particular, the failure of the fuel pump is the contamination of fuel with large or small particles, as well as the wear of the structural elements of the EFP. The purpose of the study is to determine the technical condition of electric fuel pumps of motor vehicle engines based on the use of testing technologies. The paper discusses theoretical and experimental studies of the fuel system of motor vehicle engines: the change in the current consumption rate of the EFP depending on the degree of contamination of series elements in the system and leaks in the injection unit of the EFP.